2020
DOI: 10.1186/s43058-020-00070-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of an evidence-based practice environment: an interpretive description

Abstract: Background Despite the available research to inform nursing practice, many patients still fail to receive evidence-based care. Several evidence-based practice (EBP) models have been developed to guide nurses through the steps in the process, yet these models have not been uniformly adopted or consistently used. The original purpose of this research was to gather perspectives and experiences of nurses using the Iowa Model of EBP to help inform its introduction into other practice settings. As a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Additionally, the majority of nurses indicated that their hospitals support EBP by providing EBP trainings. Hospital work environment support for EBP in the form of education, hands-on training, and a culture that encourages EBP were determinants of EBP supportive environment [ 38 ]. Our study was one of the few studies that examined staff nurses’ perceptions of EBP nursing leadership support and work environment support and their relations with nurses’ EBP competencies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the majority of nurses indicated that their hospitals support EBP by providing EBP trainings. Hospital work environment support for EBP in the form of education, hands-on training, and a culture that encourages EBP were determinants of EBP supportive environment [ 38 ]. Our study was one of the few studies that examined staff nurses’ perceptions of EBP nursing leadership support and work environment support and their relations with nurses’ EBP competencies.…”
Section: Discussionmentioning
confidence: 99%
“…Abuhammad al et al [35] study conducted in the same middle eastern region concurred the same results even emphasizing that showed the highest concerns on the topic. Duff et al [22] and Ozga et al [15] studies showed conforming these barriers results thereby stating the importance of education, hands-on training and knowledge infrastructure to be as critical as active team facilitation by senior nurses and other administration officers who all can make that big difference in overcoming this particular research utilization barriers. Another study plainly stated access to literature as a major problem and its provision as part of professional education may be a way to acquire knowledge and appropriately utilize current innovations [36].…”
Section: Discussionmentioning
confidence: 89%
“…The professional development or continuing education of nurses through research utilization has an inherent power to increase quality of healthcare [21]. In the United States, research utilization was included in job description and nurses who utilized research to solve clinical problem were recognized and rewarded [22]. This could be the pandemic situation considering the perception of respondents about research utilization.…”
Section: Discussionmentioning
confidence: 99%
“…In United States healthcare delivery organizations, 40% of patients do not receive evidence-based care, ~25% of patients are harmed, and at least 30% of annual healthcare spending is wasted ( 1 – 3 ). Harm events include medication errors, injuries, infection, prolonged hospitalization, or other unintended consequences ( 2 ).…”
Section: Introductionmentioning
confidence: 99%